2006
DOI: 10.1007/s00508-006-0609-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of IgG antibodies to pertussis toxin in the Slovene population

Abstract: The study demonstrated an early decline of anti-PT IgG after vaccination. According to the serological profile, school-age children and adolescents have the highest rate of infection. The large proportion of seropositive adults indicates that reinfection with B. pertussis is relatively common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Similar to most studies, we found no significant difference in the level of pertussis antibodies between boys and girls (17,19). However in one study girls had higher antibody levels than boys; however, the authors did not discuss any reasons for this difference (9).…”
Section: Discussionsupporting
confidence: 70%
“…Similar to most studies, we found no significant difference in the level of pertussis antibodies between boys and girls (17,19). However in one study girls had higher antibody levels than boys; however, the authors did not discuss any reasons for this difference (9).…”
Section: Discussionsupporting
confidence: 70%
“…Gender did not influence the seroimmunity in our study; the same was reported by several other investigators. [23][24][25][26] In the current study, serum pertussis IgG titres increased with age among the infants' group being lowest below 6 months of age and higher in the 12 to 24 months old which is expected due to the receival of booster doses of the vaccine. A relevant study showed that pertussis antibody levels >30 U/ml were observed with higher frequency in infants younger than 2 years of age who completed the vaccination schedule .…”
Section: Discussionmentioning
confidence: 51%
“…27 Another study revealed that vaccinated 1-2-year-old infants and 17-18-year-old adolescents had the highest serum pertussis IgG titers. 24 An interesting observation in a group of Turkish children was that pertussis antibodies increased after the age of 6 years and a further increase was observed between 7 and 12 years. Since there is no booster against pertussis at this age, this increase probably reflects the acquisition of natural immunity following the beginning of elementary school, where children join a new crowded community with higher rates of exposure to communicable diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Seroprevalence studies have shown increasing susceptibility of adolescents and younger adults for pertussis infection [27]. Epidemiological data have demonstrated a marked shift in age distribution among pertussis cases, with a rise in the number of cases among school children and adolescents [28]. Our finding of a high percentage of students who were seropositive for pertussis probably reflects reinfections.…”
Section: Discussionmentioning
confidence: 78%